NUTRISI SAAT KEHAMILAN DIMASA PANDEMI COVID-19 - Azizah, Ninik; Fatmawati, Diah Ayu (Universitas Pesantren Tinggi Darul Ulum, 2020)
AbstractÂ Pregnancy is a time when there is a fetus in a woman's womb which occurs because of the fertilization process after the meeting of the sperm and egg cells. COVID-19 has become the main pathogen of an emerging respiratory disease outbreak. They are members of this large family of viruses that can cause respiratory, enteric, liver and neurological diseases in a wide variety of animal species, including camels, cattle, cats and bats. To date, seven human CoV (HCV) - capable of infecting humans have been identified. Thus, a pregnant woman needs more nutrition or nutrition than normal conditions to meet the health of the pregnant woman herself and the baby she is still carrying with the current Covid-19 pandemic. This literature study uses the method of collecting data from computerized database tracking / systematic search studies (Pubmed, BMC, Cochrain review and Google Scholar), in the form of research journals and review articles. Micronutrients are one of these immune supplements, and their efficacy has been shown with other viral infections. A pregnant woman needs more nutrition or nutrition than normal conditions to meet the health of the pregnant woman herself and the baby she is still carrying with the current COVID-19..Â Keywords: Nutrition, Pregnancy, Covid-19